2011
DOI: 10.1002/cne.22534
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor type 1 expression during postnatal development of the rat retina

Abstract: Cannabinoid receptor type 1 (CB1R) participates in developmental processes in the central nervous system (CNS). The rodent retina represents an interesting and valuable model for studying CNS development, because it contains well-identified cell types with clearly established and distinct developmental timelines. Very little is known about the distribution or function of CB1R in the developing retina. In this study, we investigated the expression pattern of CB1R in the rat retina during all stages of postnatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 139 publications
7
46
0
1
Order By: Relevance
“…These results summarize results published in several articles [43,49,50,[55][56][57]. OS, photoreceptor outer segments; IS, photoreceptor inner segments; ONL, outer nuclear layer; ONL, outer plexiform layer; INL, inner nuclear layer; IPL, inner plexiform layer; GCL, ganglion cell layer.…”
Section: Electroretinography In Monkeyssupporting
confidence: 86%
“…These results summarize results published in several articles [43,49,50,[55][56][57]. OS, photoreceptor outer segments; IS, photoreceptor inner segments; ONL, outer nuclear layer; ONL, outer plexiform layer; INL, inner nuclear layer; IPL, inner plexiform layer; GCL, ganglion cell layer.…”
Section: Electroretinography In Monkeyssupporting
confidence: 86%
“…The staining obtained with the two antibodies in the rat was similar to that previously reported in the mouse 6,27,30) and rat 11,31) .…”
Section: Glutamine Synthetase (Gs)supporting
confidence: 86%
“…Firstly, although cannabinoid receptor mRNAs and proteins are expressed in rat Mu¨ller cells (Buckley et al, 1998;Porcella et al, 1998) (Fig. 7), the density of the receptors is lower in adult animals (Zabouri et al, 2011). It seems likely that the effects by activation of these receptors could not be detected.…”
Section: Cannabinoid Modulates Ca 2+ Channelsmentioning
confidence: 97%
“…By activating the specific cannabinoid receptors, mainly the CB1 receptor (CB1R), eCBs, such as anandamide (AEA) and 2-arachi donoylglycerol (2-AG), and CB1R agonist WIN55212-2 modulate the voltage-gated K + and Ca 2+ channels in a variety of retinal neurons (Straiker et al, 1999a;Yazulla et al, 2000;Fan and Yazulla, 2003;Straiker and Sullivan, 2003;Lalonde et al, 2006). In regard to Mu¨ller cells, it is reported that CB1Rs are expressed in the cells of goldfish (Yazulla et al, 2000) and Long-Evans rats (Zabouri et al, 2011). However, it has not been clearly established whether cannabinoid agonists may modulate the Ca 2+ channels of Mu¨ller cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation